Electrochemical Determination of Norepinephrine by Means of Modified Glassy Carbon Electrodes with Carbon Nanotubes and Magnetic Nanoparticles of Cobalt Ferrite - Queiroz, Daniely Ferreira de; Lima Dadamos, Tony Rogerio de [UNESP]; Spinola Machado, Sergio Antonio; Utrera Martines, Marco Antonio (Mdpi, 2018)
This study describes the electrochemical preparation of the electrocatalytic oxidation/reduction of noradrenaline in modified glassy carbon of cobalt ferrite nanoparticles and carbon nanotubes (GC/MWCNT/FCo98). The cobalt ferrite powder was characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The optimum conditions found in an electrode composition were 4 mu L of cobalt ferrite and 10 mu L of carbon nanotubes in 0.1 mol L-1 PBS at pH 7.0. The electrode displays electrochemical behavior in a wide potential range (-0.4 to 1.0 V vs. Ag/AgCl), high conductivity, and electrode stability/durability in 0.1 mol L-1 PBS. Catalytic oxidation of noradrenaline was performed at the unmodified GC electrode at +0.60 V vs. Ag/AgCl and current of 0.17 mu A and modified GC with cobalt ferrite nanoparticles and carbon nanotubes at +0.54 V vs. Ag/AgCl and current of 0.23 mA. With regard to the anodic peak current (I-pa) versus noradrenaline concentration by means of the amperometric method at the modified electrode, (which is linear in the 0.16 and 1.91 mmol L-1 concentration range), the concentration limit was 0.76 mu mol L-1. In this way, the modified electrode GC/MWCNT/FCo98 was found to be a promising application for the determination of this neurotransmitter in the area of neuroscience.
Keywords: electrode modified; cobalt ferrite; noradrenaline